An Aerodynamic Extension for Motion Planning with Dynamics Awareness in Aerial Long-Reach Manipulators. (19th September 2020) - Caballero, Alvaro; Sanchez-Cuevas, Pedro J.; Bejar, Manuel; Heredia, Guillermo; Trujillo, Miguel A.; Ollero, Anibal
Abstract : This paper presents a novel method for motion planning of aerial long-reach manipulators that considers the aerodynamic effects generated by close surfaces in the trajectory generation process. The aerial manipulation system consists of a multirotor equipped with a robotic long-reach arm that enables multidirectional inspection and also increases considerably the safety distance between the rotors and the inspected elements. Since these systems operate in the proximity of elements that can modify significantly the rotors' airflow, the inclusion of Aerodynamics Awareness within the motion planning process is required to ensure robust obstacle avoidance. To this end, a proper characterisation of the aerodynamic effects based on both theoretical and experimental considerations has been derived. This characterisation is taken into account in the trajectory generation process to discard states whose associated aerodynamic phenomena are not well compensated by the system controller and to explore alternatives that lead to the most efficient trajectories within the area of safe operation. Moreover, the motion planner also stands out for three other relevant features: the joint consideration of the multirotor and the robotic long-reach arm, the generation of efficient trajectories in terms of energy consumption, and the Dynamics Awareness of the strong coupling between the aerial platform and the robotic arm. The resulting motion planner has been successfully tested in a simulated environment that faithfully reflects an application scenario strongly affected by aerodynamic effects: the inspection of bridges to find potential cracks in the surface of pillars.